2022
DOI: 10.12998/wjcc.v10.i11.3449
|View full text |Cite
|
Sign up to set email alerts
|

Association of chronic obstructive pulmonary disease with mild cognitive impairment and dementia risk: A systematic review and meta-analysis

Abstract: BACKGROUND Chronic obstructive pulmonary disease (COPD) is a common public health issue that has been linked to cognitive dysfunction. AIM To investigate the relationship between COPD and a risk of mild cognitive impairment (MCI) and dementia. METHODS A comprehensive literature search of the PubMed, Embase, Google Scholar, and Cochrane Library electronic databases was conducted. Pooled odds ratios (OR) and mean differences (MD) with 95% confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…COPD is expected to be the third leading cause of death by 2030 [82]. A recent systematic review and meta-analysis found a strong correlation between COPD and increased incidence of MCI (OR = 2.11, 95%CI: 1.32-3.38) [83]. Other researchers have suggested that the prevalence of cognitive dysfunction in COPD patients is about 56.7%, four times higher than in non-COPD patients, including attention, learning, processing speed, visuospatial memory, language, and executive functioning [84].…”
Section: Lung Healthmentioning
confidence: 99%
“…COPD is expected to be the third leading cause of death by 2030 [82]. A recent systematic review and meta-analysis found a strong correlation between COPD and increased incidence of MCI (OR = 2.11, 95%CI: 1.32-3.38) [83]. Other researchers have suggested that the prevalence of cognitive dysfunction in COPD patients is about 56.7%, four times higher than in non-COPD patients, including attention, learning, processing speed, visuospatial memory, language, and executive functioning [84].…”
Section: Lung Healthmentioning
confidence: 99%
“…functions (Simargi et al, 2022;Zhao and Zhou, 2022), anxiety (Martínez-Gestoso et al, 2022), and depression (Peiffer et al, 2021;Martínez-Gestoso et al, 2022). Long-term Oxygen Therapy (LTOT) has been found to improve the quality of life (Pavlov et al, 2018).…”
mentioning
confidence: 99%